Kontaminasi bakteri Eschericia coli pada makanan yang dijual di pasar tradisional Yogyakarta - Amyati Amyati (STIKes Surya Global Yogyakarta, 2020)
Food based on health standards become an important need in order to not health problems. The principles of food sanitation are very important in the food making process. The food must be safe for eaten. Based on observations, the principles of food sanitation are still not being applied by traders in the Kotagede Market area of Yogyakarta. Many foods are sold open and mix with other merchandise, allowing contamination. Health problems can occur because of not paying attention to the principles of food sanitation, such as diarrhea, vomiting and other digestive problems. To determine the quality of the food sold, it is necessary to check and supervise the food, one of which is by testing microbiologically. The purpose of this study is to determine the contamination ofEschericia coli bacteria in the food. This type of research was descriptive qualitative. This research was conducted by examining the food sold in the Kotagede Market area of Yogyakarta. The population in this study was all the food sold in the Kotagede Market area of Yogyakarta. The sampling technique used purposive sampling. The sample in this study were 10 types of food. The data were analyzed using the MPN (most probable number) method. Samples were examined at the BBTKL PP Laboratory, Yogyakarta Special Region Health Service. The results of laboratory tests on 10 food samples sold showed that all food was contaminated with Escherichia coli bacteria at Kotagede Market area of Yogyakarta.